Signifikansi Kebudayaan dalam Pendidikan : Refleksi Identitas Keberagaman Siswa di Ruang Kelas - Heni Rahmawati; Rosyidatul Afifah; Fitri Nur Cholifah; Arif Rahman (Kayon Media, 2021)
Abstract: : This study was conducted to gather sufficient information on the significance of culture in education by reflecting on the diversity identity of students in the classroom. The method used in this study is through the library (Library Search) which includes qualitative research carried out by reading literature, such as journals, books or magazines and other sources. The results of this study indicate that students in the classroom have a diversity of races, ethnicities, cultures, religions, languages, and groups, so multcultural education is very important to be reflected on students in the classroom, with this understanding it is hoped that students can carry out the Indonesian motto,